Sun of Righteousness, Arise! The Freedom of a Christian—Then and Now—for the Perpetrators and for the Victims of Sin - Moltmann, Jürgen (Theology today, 2012)
The following is a lecture, which Prof. Dr. Jürgen Moltmann gave for the Reformation Day Celebration at Emory University, Atlanta, Georgia. It has an ecumenical direction, beginning with Martin Luther and ending with Charles Wesley’s verse “Sun of Righteousness, Arise!” The lecture moves from Martin Luther in the sixteenth century and his treatise on “The Freedom of a Christian” to Martin Luther King Jr. in the twentieth century, and the inscription on his grave: “Free at last. At last free!”